The Difference in The Level of Dental Caries Knowledge Based on Age and Gender Among Students Aged 13-15 Years - Farani, Wustha; Salsabila, Assysaffa Ananda (Dentika: Dental Journal, 2023)
According to Riskesdas 2018, caries or cavities show that 65.5% of children aged 12 years and 67.4% of children aged 15 years’ experience this condition. Despite its high prevalence, reports regarding the status of dental caries and the importance of oral hygiene in adolescents are still limited. The Islamic boarding school where several teenagers live has an independent and self-caring nature, which causes oral and dental health to be neglected. This study aims to determine differences in the level of knowledge of dental caries based on age and gender in students aged 13-15 years at the Ma'ahid Kudus Madrasah Tsanawiyah (MTS) Islamic Boarding School. Analytical observational research with cross-sectional methods. The selection of respondents was carried out using a proportional stratified random sampling technique. There was a significant difference in the level of knowledge of dental caries with age (p<0.05), and there was no difference based on gender (p>0.05). Based on the research results, the level of knowledge about dental caries of students aged 13-15 years at the MTS Maahid Kudus Islamic Boarding School is mostly in the good category.